Displacement reconstruction of beams subjected to moving load using data fusion of acceleration and strain response. (1st October 2022) - He, Wen-Yu; Liu, Peng; Cheng, Hua-Cai; Li, Zi-Bing; Bu, Jian-Qing
Highlights: A moving load induced displacement reconstruction method using data fusion of acceleration and strain response. A correction factor is proposed to determine the neutral axis position of the cross-section. The proposed correction factor can determine the position of the neutral axis with high accuracy. The proposed method can obtain more accurate reconstruction displacement than using the acceleration or the strain alone. Abstract: Displacement response induced by moving load is important for health monitoring and safety assessment of beams. It contains displacement representing the high frequency part and pseudo-static displacement (PSD) representing the low frequency part. It is normally difficult to reconstruct the PSD due to its approximately zero frequency and inaccurate assumption of the neutral axis position of the structural cross-section. This paper presents a moving load induced displacement reconstruction method using data fusion of acceleration and strain response with special attention on PSD extraction. Firstly, the displacements are derived from the acceleration and strain, which are deemed as the acceleration-derived displacement (ADD) and the strain-derived displacement (SDD), respectively. Subsequently, a correction factor is proposed based on the ADD and SDD to determine the neutral axis position of the structural cross-section. Then the PSD is extracted from the SDD based on the correction factor and a designed low-pass filter. Finally, the performance of proposed method is investigated by numerical and experimental examples. The results manifest that the correction factor can determine the neutral axis position with high accuracy, and the proposed method can obtain more accurate reconstructed displacement than using the acceleration or the strain alone.